Transparent exopolymer particles (TEP) formation from alginate blocks and their effects on membrane fouling - Meng, Shujuan (2016)
Transparent exopolymer particles (TEP) have drawn ample attention since they were introduced into the field of membrane fouling. TEP have been described as a class of transparent particulate acidic polysaccharides that can be stained by alcian blue. So far, it has been reported that TEP are involved in the fouling development in various membrane systems including membrane bioreactor (MBR), microﬁltration (MF), ultraﬁltration (UF) and reverse osmosis (RO). The extensive involvement of TEP in membrane fouling is probably due to following four reasons: (i) TEP are typically stickier than other particles in water, leading to their easy accumulation and difficult removal in membrane systems; (ii) TEP are deformable, thus they could pass through membrane with a pore size smaller than their dimension; (iii) TEP can flex, fragment and disperse through membrane pores of MF and UF and then reassemble in the filtrate to form large size network before reaching the RO membrane modules and (iv) Highly colonized by microbes, TEP could transport bacteria from water phase to membrane surface by adhesion, accelerating the formation of biofilm on the membrane. It should be realized that the formation of TEP mainly depends on the type of precursor materials and chemistry conditions of bulk solution. Therefore, this study was aimed to investigate the TEP formation from alginate blocks under different chemistry conditions and the role of TEP in membrane fouling development. In the first phase of study, alginate blocks and their effect on membrane fouling was investigated. Alginate as a common and widespread polysaccharide has been reported to generate TEP-like particles that can be stained by alcian blue. Alginate is composed of two different monomers, namely M ((1→4) linked β-D-mannopyranuronic acid) and G ((1→4) linked α-L-gulopyranuronic acid) which are randomly arranged into MG-, MM- and GG-blocks. Results showed the severest fouling in the filtration of MG-block, and the least flux decline in the filtration of MM-block. The initial pore blocking was found to be responsible for the fouling observed in MG-block filtration, while the cake layer formed on membrane surface during the MM-block filtration could serve as a pre-filter that prevented membrane from further pore blocking. TEP were found to form through aggregation or cross-link of alginate blocks. It was observed that more TEP were produced from MM-blocks than from MG-blocks in solutions. As TEP were bigger than original alginate blocks, they could facilitate the formation of cake layer on membrane surface, which explained why cake resistance was dominant in the filtration of MM-blocks as compared to MG-blocks. The analysis by the extended Derjaguin-Landau-Verwey-Overbeek (XDLVO) theory further revealed that MM-blocks had lowest cohesive interaction energy among all three alginate blocks, which favoured aggregation of MM-blocks, and ultimately leading to the formation of more TEP. This study provided insights into the TEP formation from different alginate blocks and revealed the role of TEP in microfiltration. The importance of calcium ion in TEP formation has been reported before. In this phase of study, the TEP formation from alginate blocks was investigated with various calcium concentrations and the effect of TEP on membrane fouling development was further studied. Results showed that calcium ion had the most serious effects on GG-blocks and significantly promotes the formation TEP from GG-blocks which in turn led to rapid formation of thick cake layer on membrane surface during the filtration of GG-blocks. As for MM-blocks, it was found that the formation of TEP was proportional to the Ca2+ concentration in MM-blocks solution, while the membrane fouling was enhanced by Ca2+ in the filtration of MM-blocks solution. Unlike MM- and GG-blocks, MG-blocks were nearly not affected by addition of calcium ion, as the result, there was no significant increase in TEP. The initial fouling rates and the mass of foulants deposed on the membrane surfaces further revealed a close correlation between the TEP concentration and the membrane fouling propensity. This study offers deep insights into the development of membrane fouling by different alginate blocks in the presence of calcium ion, and suggests that TEP formed from alginate blocks played a very significant role in the fouling development. TEP formation at various sodium ion concentrations with a fixed calcium ion concentration was investigated. Results showed that increasing sodium ion concentration largely reduces the TEP production in all three types of alginate blocks, which further prevented the cake layer development on the membrane surface. Competition between calcium ions and sodium ions is likely responsible for the reduction of TEP formation from alginate blocks. At high sodium ion concentration, the bonding opportunity of alginate blocks to calcium ions is out-competed by sodium ions, thus decreasing the formation of TEP. These results suggest that a more abundant TEP could be expected in freshwater than in seawater at the same level of precursor materials. In addition, results further revealed that the TEP formation is a function of Ca2+ concentration and the phases pertaining to TEP development can be clearly divided into three phases. At low Ca2+ concentration, TEP formation was not sensitive to Ca2+ concentration, while at medium Ca2+ concentration, the formation of TEP appeared to be proportionally related to Ca2+ concentration. At high Ca2+ concentration, further increase of the Ca2+ concentration had insignificant effect on TEP formation from GG-blocks at a given concentration of GG-blocks. Besides, increasing ionic strength can compress the electrical double layer of alginate blocks, thus promoting the crosslink of alginate blocks and producing more TEP. These results showed that the formation of TEP is mainly subject to the chemistry condition of bulk solution at a fixed concentration of precursor materials. In conclusion, this study clearly showed the significant role of TEP in membrane fouling and showed the TEP formation from precursors at diverse chemistry conditions.